Multiple interleaved mode saturation (MIMOSA) for B1+ inhomogeneity mitigation in chemical exchange saturation transfer. Issue 2 (19th April 2019) - Liebert, Andrzej; Zaiss, Moritz; Gumbrecht, Rene; Tkotz, Katharina; Linz, Peter; Schmitt, Benjamin; Laun, Frederik B.; Doerfler, Arnd; Uder, Michael; Nagel, Armin M.
Abstract : Purpose: To mitigate B 1 + inhomogeneity in quantitative CEST MRI at ultra‐high magnetic field strengths (B0 ≥ 7 Tesla) using a parallel transmit system. Methods: Multiple interleaved mode saturation employs interleaving of 2 complementary phase sets during the saturation pulse train. Phase differences of 45° (first mode) and 90° (second mode) between 2 adjacent transmitter coil channels are used. The influence of the new saturation scheme on the CEST contrast was analyzed using Bloch‐McConnell simulations. The presented method was verified in phantom and in vivo measurements of the healthy human brain. The relayed nuclear Overhauser effect was evaluated, and the inverse magnetic transfer ratio metric was calculated. Results were compared to a published B 1 + correction method. All measurements were conducted on a whole‐body 7 Tesla MRI system using an 8 transmitter and 32 receiver channel head coil. Results: Simulations showed that the inverse magnetic transfer ratio metric contrast of relayed nuclear Overhauser effect shows a smaller dependency on the relative amplitudes of the 2 different modes than the contrasts of Cr and amide proton transfer. Measurements of an egg white phantom showed markedly improved homogeneity compared to the uncorrected inverse magnetic transfer ratio metric (relayed nuclear Overhauser effect) images and slightly improved results compared to B 1 + corrected images. In vivo multiple interleaved mode saturation images showed similar contrast compared to B 1 + corrected images. Conclusion: Multiple interleaved mode saturation can be used as a simple method to mitigate B 1 + inhomogeneity effects in CEST MRI at ultra‐high magnetic field strengths. Compared to previous B 1 + correction methods, acquisition time can be reduced because an additional scan, usually required for B 1 + correction, can be omitted.